Inverse problems for Jacobi operators IV: interior mass-spring perturbations of semi-infinite systems*Research partially supported by UNAM-DGAPA-PAPIIT IN105414. (5th April 2017) - del Rio, Rafael; Kudryavtsev, Mikhail; Silva, Luis O
Abstract: This work gives results on the interplay of the spectra of two Jacobi operators corresponding to an infinite mass-spring system and a modification of it obtained by changing one mass and one spring of the system. It is shown that the system can be recovered from these two spectra. Necessary and sufficient conditions for two sequences to be the spectra of the mass-spring system and the perturbed one are provided.